Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1021/nl903104k
|View full text |Cite
|
Sign up to set email alerts
|

Photocurrent Induced by Nonradiative Energy Transfer from Nanocrystal Quantum Dots to Adjacent Silicon Nanowire Conducting Channels: Toward a New Solar Cell Paradigm

Abstract: We report the observation of photocurrent in silicon nanowires induced by nonradiative resonant energy transfer (NRET) from adjacent layers of lead sulfide nanocrystal quantum dots using time-resolved photocurrent measurements. This demonstration supports the feasibility of a new solar cell paradigm (Lu, S.; Madhukar, A. Nano Lett. 2007, 7, 3443-3451) that exploits NRET between efficient photon absorbers and adjacent nanowire/quantum well high-mobility charge transport channels and could offer a viable alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
83
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 9 publications
1
83
0
Order By: Relevance
“…Further evidence supporting the potential feasibility of the solar cell paradigm based on the RET mechanism from deposited PbS QDs on the top of silicon nanowires, was reported the same year by S. Lu et al [13]. Photocurrent time resolved measurements were performed and showed a clear increase in the photocurrent at delay times of ten to hundreds nanosecond in the case of the hybrid structure in comparison with the bare silicon nanowire structure.…”
Section: -Introductionsupporting
confidence: 56%
“…Further evidence supporting the potential feasibility of the solar cell paradigm based on the RET mechanism from deposited PbS QDs on the top of silicon nanowires, was reported the same year by S. Lu et al [13]. Photocurrent time resolved measurements were performed and showed a clear increase in the photocurrent at delay times of ten to hundreds nanosecond in the case of the hybrid structure in comparison with the bare silicon nanowire structure.…”
Section: -Introductionsupporting
confidence: 56%
“…Förster-type NRET is a dipole-dipole interaction between resonant donor and acceptor species and has a well-defined distance dependence [20]. NRET has been demonstrated in a large range of material systems, with potential for LED [9,[21][22][23][24][25] and light harvesting applications [2,3,13,[26][27][28][29][30][31][32][33]. QDs possess excellent optical properties such as broadband absorption with narrow and tunable emission profiles, giving them a distinct advantage over organic dyes [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…They proposed a solar cell design utilizing NRET and postulated an efficiency of approximately 19% assuming unity quantum yield for the QDs. Further work by that group [30] demonstrated NRET from PbS QDs to Si nanowires with efficiencies in the range 4 of 15-38%, and showed that the photocurrent due to NRET can be 3 times that due to direct light absorption in the Si nanowires for excitation near the QD absorption peak. Chanyawadee et al [2,13] micro-patterned hybrid QD-GaAs based p-i-n devices to bring QDs into close proximity with the intrinsic region of p-i-n heterostructures, and thereby benefit from efficient NRET from the QDs.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 In SiNWs under illumination, the photon energy is absorbed and generates electron-hole pairs in the nanowires, which are separated immediately by the applied potential. 21,22 The generated electrons combine with the carrier trap, while the photogenerated holes remain in the nanowires and contribute to an increase in the current. The photoresponsivity at 7 nW cm À2 of incident light and 5.0 V bias voltage has been calculated to be R (responsivity) $ 0.31 A/W.…”
Section: -3mentioning
confidence: 99%